Synchronous multiple myeloma and lung adenocarcinoma: A clinical series - Fang Ye; Huan Wang; Ningning Li; Aijun Liu; Wenming Chen (Indian Journal of Pathology and Microbiology, 2024)
Background: Multiple myeloma (MM) is characterised by an increased number of monoclonal immunoglobulin-producing plasma cells that malignantly grow in the bone marrow. Lung cancer is one of the most common malignancies and at the advanced stage may become metastatic to the bone. Rarely, MM and lung cancer are synchronously present in the same patient. Materials and Methods, Results: In this report, we describe five cases of MM synchronous with lung adenocarcinoma including λ light chain in three cases and ϰ light chain in two cases. Two patients achieved complete remission, and no progression was seen in two patients. Conclusion: In conclusion, synchronous MM and lung adenocarcinoma are clinically rare, and diagnosis should be made scrupulously based on morphology, immunology, cytogenetics, molecular biology and biopsy pathology.